Age-differences in interpreting the valence of ambiguous facial expressions: evidence for multiple contributing processes. Issue 4 (4th July 2022) - Barber, Sarah J.; Schoeke, Andrej; Mather, Mara
ABSTRACT: Surprised facial expressions, which are ambiguous in valence, are interpreted more positively by older adults than by younger adults. To evaluate the processes contributing to this age difference, we varied the spatial frequency of the surprised-face stimuli. When faces were presented in a low-spatial-frequency band, it biased participants to rate them negatively. Although this occurred for both younger and older adults, the older adults' ratings of the low-spatial-frequency faces were more positive than that of the younger adults. This suggests that there is an age-related reduction in the default negativity of interpretations. We also found that older adults, as a whole, rated the high-spatial-frequency faces more positively than did younger adults. However, this effect was eliminated for the subset of older adults with poor high-spatial-frequency perception abilities for whom these faces were difficult to perceive. Thus, older adults' more positive interpretations of surprised faces may also reflect cognitively-effortful regulatory processes.